Peran Leuit dalam Ketahanan Pangan Lokal Berkelanjutan di Kampung Nyompok Suwakan - Ismet Firdaus; Nadia Aisya Fitri; Risya Destriana Putri; Amelia Putri Pratama; Haafidzhil Arham; Indra Fata (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Leuit is a traditional Sundanese rice barn that plays a crucial role in maintaining local food security while preserving cultural values. This study aims to analyze the role of leuit in Nyompok Village, Suwakan, Lebak Regency, in supporting sustainable food self-sufficiency. The research employed a descriptive qualitative method through observation, interviews, and documentation. The findings reveal that leuit functions not only as a storage facility to secure rice during famine, natural disasters, or crop failure, but also as a symbol of social solidarity, local wisdom, and community food sovereignty. This tradition reflects the community’s strong attachment to agrarian practices inherited from their ancestors, where rice is regarded as a symbol of life and prosperity. Moreover, leuit is capable of preserving rice quality over long periods due to its eco-friendly traditional construction. However, modernization and the younger generation’s reliance on market-based systems have gradually diminished its role. Therefore, preserving leuit should be considered as an integrative strategy that ensures food security while maintaining the social, cultural, and spiritual values of the community.